2022
DOI: 10.1177/1759720x211066685
|View full text |Cite
|
Sign up to set email alerts
|

Poor health and functioning in patients with axial spondyloarthritis during the COVID-19 pandemic and lockdown: REUMAVID study (phase 1)

Abstract: Aim: To evaluate the overall health and functioning in patients with axial spondyloarthritis (axSpA) and related factors affecting these during the COVID-19 pandemic and lockdown measures. Methods: Data from 587 axSpA patients participating in the first phase (April–July 2020) of the REUMAVID study who completed the ASAS Health Index (ASAS-HI) were analysed. REUMAVID is a cross-sectional study that collects data through an online survey to assess the impact of the COVID-19 pandemic on patients with rheumatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Possibly, it forms a vicious cycle of poor physical activity, worsening disease activity, and inflammation, leading to poor control of DM. This may hold true for other inflammatory RDs if analyzed specifically in this fashion [51].…”
Section: Other Diseasesmentioning
confidence: 91%
See 1 more Smart Citation
“…Possibly, it forms a vicious cycle of poor physical activity, worsening disease activity, and inflammation, leading to poor control of DM. This may hold true for other inflammatory RDs if analyzed specifically in this fashion [51].…”
Section: Other Diseasesmentioning
confidence: 91%
“…A Spanish web-based cross-sectional observational study (REUMAVID) evaluated the effects of COVID-19 on various aspects of healthcare for RDs [51]. An analysis of 587 patients with axial spondyloarthritis was carried out of which 4.3% had DM.…”
Section: Other Diseasesmentioning
confidence: 99%
“…In March 2020, the World Health Organization declared a global pandemic caused by coronavirus disease (COVID-19) 2 , initiating a period of restrictions and multiple lockdowns, which could lead to new diseases or exacerbation of pre-existing diseases by reducing healthcare provider consultations and/or affecting mental health 3 , 4 . Ciuera et al found no evidence of worsening disease activity in axSpA during the lockdown 5 , while others demonstrated that approximately 50% of axSpA patients reported worse health status and well-being than before the pandemic 6 , 7 . As analysing web search data on health topics can contribute to a better understanding of the interest and needs on a population-level 8 , 9 , this study aimed to examine the impact of the COVID-19 pandemic on axSpA in Germany by comparing axSpA-related web searches before and during the COVID-19 pandemic (cut-off: March 2020) in terms of search content.…”
Section: Introductionmentioning
confidence: 97%